Non-human Primate Regulatory T Cells and Their Assessment as Cellular Therapeutics in Preclinical Transplantation Models - Thomson, Angus W.; Sasaki, Kazuki; Ezzelarab, Mohamed B. (Frontiers in Cell and Developmental Biology, 2021)
Nonhuman primates (NHP) are a valuable resource for addressing key issues concerning the immunobiology of regulatory T cells (Treg), their in vivo manipulation and the translation of adoptive Treg therapy to the clinic. In addition to their phenotypic and functional characterization, particularly in cynomolgus and rhesus macaques, NHP Treg have been isolated and expanded successfully ex vivo. Their numbers can be enhanced in vivo by administration of IL-2 and other cytokines. Both polyclonal and donor antigen (Ag) alloreactive NHP Treg have been expanded ex vivo and their potential to improve long-term outcomes in organ transplantation assessed following their adoptive transfer in combination with various cytoreductive, immunosuppressive and “Treg permissive” agents. In addition, important insights have been gained into the in vivo fate/biodistribution, functional stability, replicative capacity and longevity of adoptively-transferred Treg in monkeys. We discuss current knowledge of NHP Treg immunobiology, methods for their in vivo expansion and functional validation, and results obtained testing their safety and efficacy in organ and pancreatic islet transplantation models. We also consider prospects for future studies in NHP aimed at improved understanding of Treg biology, and innovative approaches to promotion and evaluation of their therapeutic potential.